New potential antitumoral fluorescent tetracyclic thieno[3,2-b]pyridine derivatives: interaction with DNA and encapsulation in nanoliposomes - Castanheira, Elisabete M. S. (2010)
This work was funded by FCT-Portugal and FEDER through CFUM, CQ-UM, Project PTDC/QUI/81238/2006 cofinanced by FCT and program FEDER/COMPETE (FCOMP-01-0124-FEDER-007467) and PhD grants of M.S.D. Carvalho (SFRH/BD/47052/2008) and R.C. Calhelha (SFRH/BD/29274/2006).